A School Story - 1951-; Tripp, Valerie; Payne, C. F. (Madison, Wis., 1986)
During World War II, nine-year-old Molly and her friends work on projects to aid the war effort.
During World War II, nine-year-old Molly goes to school and with her friends tries to aid the war effort.
Keywords: Fiction; World War, 1939-1945; Fiction; United States; School stories; Schools